1997
DOI: 10.1136/vr.140.10.253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a simplified intravenous glucose tolerance test and a reflectance glucose meter for use in cats

Abstract: A simplified intravenous glucose tolerance test has been developed for use in domestic cats and the results compared with those obtained using the standard test. The simplified test used two cephalic catheters, implanted in unsedated, unanaesthetised cats three hours before the test. Blood samples were collected before and after intravenous administration of glucose (0.5 g/kg bodyweight). Blood glucose concentration was measured with a reflectance glucose meter and an automated chemistry analyser. There were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
3
36
0
Order By: Relevance
“…Twenty micro liters of blood samples were taken from the tail vein, and blood glucose was measured with an ANTISENSE II Blood Glucose Analyzer (Sankyo Co. Ltd., Tokyo, Japan). The elimination half-life (T 1/2 ) for blood glucose was calculated by linear regression analysis of the time course of glucose concentration after glucose loading, 14,15) and seven animals were used at each time point. For analyzing metabolic functions, water, the gelatin 83.0 mg/ml free amino acid 3.1 mg/ml L-anserine 2.3 mg/ml L-carnosine 0.8 mg/ml taurine 0.7 mg/ml hexose 0.8 mg/ml phosphatidyl choline 0.4 mg/ml minerals calcium 26 g/ml iron 1 g/ml zinc 2 g/ml magnesium 32 g/ml sodium 1740 g/ml natrium 550 g/ml chlorine 1340 g/ml phosphorus 480 g/ml sulfur 500 g/ml copper 2 g/ml manganese 5 g/ml selenium 0.05 g/ml vitamins vitamin B2 1.0 g/ml vitamin B6 0.37 g/ml vitamin B12 0.002 g/ml niacin 6.4 g/ml falacin 0.15 g/ml vitamin C 15 g/ml…”
Section: Methodsmentioning
confidence: 99%
“…Twenty micro liters of blood samples were taken from the tail vein, and blood glucose was measured with an ANTISENSE II Blood Glucose Analyzer (Sankyo Co. Ltd., Tokyo, Japan). The elimination half-life (T 1/2 ) for blood glucose was calculated by linear regression analysis of the time course of glucose concentration after glucose loading, 14,15) and seven animals were used at each time point. For analyzing metabolic functions, water, the gelatin 83.0 mg/ml free amino acid 3.1 mg/ml L-anserine 2.3 mg/ml L-carnosine 0.8 mg/ml taurine 0.7 mg/ml hexose 0.8 mg/ml phosphatidyl choline 0.4 mg/ml minerals calcium 26 g/ml iron 1 g/ml zinc 2 g/ml magnesium 32 g/ml sodium 1740 g/ml natrium 550 g/ml chlorine 1340 g/ml phosphorus 480 g/ml sulfur 500 g/ml copper 2 g/ml manganese 5 g/ml selenium 0.05 g/ml vitamins vitamin B2 1.0 g/ml vitamin B6 0.37 g/ml vitamin B12 0.002 g/ml niacin 6.4 g/ml falacin 0.15 g/ml vitamin C 15 g/ml…”
Section: Methodsmentioning
confidence: 99%
“…3 However, the testing protocol and method for determining glucose concentrations in the study reported here differed from those used in previous studies. 3,6,7 To the authors' knowledge, use of the insulin tolerance test (ITT) has not been reported in cats. This test allows general assessment of insulin sensitivity by determining the decrease in plasma glucose concentration following an IV insulin injection.…”
mentioning
confidence: 97%
“…Immediately following glucose injection, 3 ml of saline solution was infused to flush the catheter. Twentyseven 1-ml blood samples were collected over the next 3 hours at 2, 3,4,5,6,8,10,12,14,16,19,22,24,25,27,30,40,50,60,70,80,90, 100, 120, 140, 160, and 180 minutes. Twenty minutes after glucose injection, regular human insulin (0.05 U/kg) was injected via the jugular catheter, followed immediately by 3 ml of saline solution.…”
mentioning
confidence: 99%
“…These methods may be used to diagnose small intestinal malabsorptive diseases, detect hyperinsulinism, differentiate type I from type II diabetes mellitus, and as a research tool. [3][4][5][6] Although these tests are useful, there are several potential confounding effects associated with the procedures that must be considered when data are being reviewed.…”
Section: Introductionmentioning
confidence: 99%